Perfil lipídico y su relación con la presión arterial, en pacientes hipertensos del Subcentro de Salud Motupe - Armijos Delgado, Jhuliana Pamela (2022)
Arterial hypertension (HTN) is the main mortality factor, pince it is considered one of the biggest public health problems worldwide. It is associated with unhealthy lifestyles such as: sedentary lifestyle, decreased physical activity, high salt intake, alcohol consumption, tobacco and stress, this together with dyslipidemias (elevated levels of the lipid profile) constitute a clónica marker of diseases cardiovascular. That is why the lipid profile has been considered, to determine the state of metabolism of body lipids, commonly in blood serum. Thus, this research work aimedto correlate the high levels of the lipid profile with blood pressure in hypertensive patients who attend the Motupe Health Subcenter, the research has a quantitative, nonexperimental, correlational cross-sectional approach, where the following results were obtained: it was determined that of the 130 hypertensive patients, 30.7% (n=40) 3 have high cholesterol, 38.5% (n=50) have high LDL-cholesterol, 67.7% (n=88) have high triglicéridos, while 22.3% (n= 29) have low HDL-cholesterol values, being themale sex and the age of 60 to 69 years the most frequent affected by the high levels of the lipid profile, when establishing the relationship it can be said that the high levels of the lipid profile are related to blood pressure, For this reason, hypertensive patients must have their lipid profile constantly evaluated to assess the risk of developing cardiovascular disease as a result of a disorder in lipid metabolism